Home-garden connectivity rather than tree-cover connectivity facilitates biodiversity in fragmented tropical forest landscapes - Sun, Ping; Baumann, Matthias; Kaplin, Beth A.; Kuemmerle, Tobias; Fischer, Joern (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Forest landscape restoration (FLR) has emerged as a global strategy to address forest fragmentation and degradation, yet, its ecological effectiveness at local scales remains uncertain. Further, many FLR interventions focus on tree planting, while overlooking other tree-rich systems such as home gardens. This study focused on the Afromontane rainforest landscape of western Rwanda—a biodiversity-rich region under intense anthropogenic pressure. As tree plantations and home gardens represent the dominant land use types in the study area, our research aimed to assess their respective roles in supporting landscape connectivity and biodiversity. First, we evaluated how tree cover and home gardens contribute to landscape connectivity by applying circuit theory through Omniscape. Subsequently, we examined the relationships between tree-cover connectivity, home-garden connectivity, and the richness and diversity of woody plants and birds, using data collected from 91 field sites. Results Tree-cover connectivity was negatively correlated with the richness and diversity of woody plants and birds. This suggested that increased connectivity through mostly exotic trees did not translate into habitat connectivity for biodiversity. In contrast, home-garden connectivity was positively correlated with the richness and diversity of woody plants and birds. This highlighted the possible beneficial role of home gardens as ecological stepping stones. We recommend that restoration efforts prioritize the protection of remaining natural forests, which are irreplaceable for sustaining native biodiversity. Complementary FLR strategies should promote the regeneration of secondary forests dominated by indigenous tree taxa and the expansion of biodiverse agroforestry systems, such as home gardens.
Keywords: Biodiversity; Forest Landscape Restoration; Home Garden; Landscape Connectivity; Stepping Stone